Nucleotide sequence of the EcoRI E fragment of adenovirus 2 genome. - Hérissé, J (1981)
The entire nucleotide sequence of the Ad.2 EcoRI E fragment has been determined using the Maxam and Gilbert method. This sequence of 2222 bp, which maps between coordinate 83.4 and 89.7 contains information relative to the early 3 region and to the fiber gene. Altogether with fragment EcoRI D which has been recently sequenced, they cover the entire Early 3 region in which several mRNA were mapped. The aminoacid sequence of the 16K and 14K protein is deduced. The localization of the 14.5K mRNA directing the synthesis of the third E3 known protein is discussed, as well as the hypothetical existence of three other early 3 proteins, which would have a molecular weight of 11K. The initiator ATG triplet of the fiber protein has been found at coordinate 86.1, it is followed up to the end of the fragment by an open reading frame allowing deduction of 80% of the aminoacid sequence of this protein. Sequences known to be frequently present at the border of exon sequence were used to tentatively localize the additional "Z" late leader.